PENERAPAN STRATEGI THINK-TALK-WRITE (TTW) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK KELAS VII4 SMP NEGERI 3 TAMBANG - Julinar '; Kartini '; Syofni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on ability of understanding mathematical. This research aims to improve the learning process and improve ability of understanding mathematical students in class VII4 SMP Negeri 3 Tambang by the implementation of the strategy Think-Talk-Write (TTW). This research is a class action research consist of two cycles. The subject of this research were the students of class VII4 SMP Negeri 3 Tambang that consist of 19 boys and 11 girls. The instruments of data collection in this research were observation sheet, students mathematical understanding of first ability tests  and students mathematical understanding of ability tests. The results of this research showed the activity of teacher and students performing well according to plan. Most students look to actively participate in the learning process. Based on data analysis ability of understanding mathematical students in classical class VII4 SMP Negeri 3 Tambang, obtained an average value ability of understanding mathematical students in the classical style on the first cycle is higher than the average value on first tests ability of understanding mathematical students and the average value ability of understanding mathematical students classically on the second cycle is higher than the average value in first cycle. Average value ability of understanding mathematical students classical students has increased from the first tests to the first cycle of 13.89. The average value ability of understanding mathematical students classical has increased from the first cycle to the second cycle at 5.46. It shows ability of understanding mathematical students with implementation of Think-Talk-Write (TTW) strategy is increased. Based on the result of this research could be concluded that the implementation of Think-Talk-Write (TTW) strategy can improve the learning process and improve ability of understanding mathematical of class VII4 of SMP Negeri 3 Tambang in the second semester academic years 2015/2016.